The Impact of Cross-Cultural Differences on Project Performance: A Study of Power Sector Development Operation and Electricity Sector Development Project in Uganda - Gubala, Fredrick; Awolusi, Olawumi Dele (Journal of Education and Vocational Research, 2020)
The purpose of this research was to establish a relationship between people’s cultural attributes, multinational project management processes, project technologies and project performance in Uganda’s energy sector concerning the practice during the implementation of the Power Sector Development Operation (PSDO) and Electricity Sector Development Project (ESDP) as case studies. The study employed a comprehensive survey design which mostly quantitative thus requiring the collection and analysis of data. It tangled both analytical and descriptive research designs. The research targeted 136 project beneficiaries or ‘project clients’ spread across the various target areas. The simple random sampling method was employed. Data compiled was reviewed to fill any gaps for incompleteness and inconsistency. This was to make ensure the exactness of the material provided acquired from the participants, through the continued reviews and comments provided by the Supervisor. Data was re-organized and software called the Statistical package. For social scientists (SPSS) was used to enter the data and analyze it, the results indicated a strong positive correlation people’s cultural attributes and project performance, multinational project management processes and project performance and between project technologies and project performance(r = .535** p ? 0.01, r = .758** p ? 0.01 and r = .656** p ? 0.01) correspondingly. It was concluded that people’s culture attributes, multinational project management and project technologies are pre-requisites for effective project performance in the Power Sector Development Operation Project and Electricity Sector Development project in Uganda and that Project technologies are a better predictor of project performance. The suggestion or recommendation for project managers to ensure that they progress implementation of their projects, peoples culture attributes, multinational project management and project technologies need to be enhanced through training of project staff and effective involvement of the communities.